The Influence of Price, Food Quality, Service, and Environment on Loyalty through Satisfaction and Happiness - Windy Freshia Luhana; Hananiel Mennoverdi Gunawan (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This research aims to determine the influence of perceived price, quality of food, quality of service, quality of the physical environment on customer loyalty through the mediation of satisfaction and happiness of Momoyo Pucang Anom customers in Surabaya. The research was conducted quantitatively. The data used is primary data with a sample of 101 respondents. Research data was processed using Partial Least Square Method analysis using the PLS application. The test results found that perceived price, quality of food, quality of service, quality of the physical environment had an effect on customer loyalty. Research also finds that customer satisfaction and customer happiness are also able to mediate the relationship between perceived price, quality of food, quality of service, quality of the physical environment on customer loyalty. Happy and satisfied customers are more likely to stay loyal, return, and recommend the restaurant to others. It is critical for managers to consistently employ a variety of tactics to meet customer needs and foster a sense of happiness and satisfaction to foster customer loyalty. As a result, businesses that have difficulty retaining customers can make more money by retaining loyal customers